Numerical investigations on the heat transfer enhancement in a wavy channel using nanofluid - Ahmed M.A.; Shuaib N.H.; Yusoff M.Z. (2023)
In this paper, laminar copper-water nanofluid flow and heat transfer in a two-dimensional wavy channel is numerically investigated. The Reynolds number and nanoparticle volume fraction considered are in the ranges of 100-800 and 0-5% respectively. Numerical solutions are obtained by solving the governing equation of stream function, vorticity transport and energy in curvilinear coordinates using the finite difference method. The effects of nanoparticle volume fraction, the wavy channel amplitude and wavelength and the Reynolds number on the local skin-friction coefficient, local and average Nusselt number and the heat transfer enhancement are presented and discussed. Results show that the friction coefficient and Nusselt number increase as the amplitude of wavy channel increases. As the nanoparticle volume fraction increases, the Nusselt number is found to be significantly increased, accompanied by only a slight increase in the friction coefficient. In addition, it was found that the enhancement in heat transfer mainly depends on the nanoparticle volume fraction, amplitude of the wavy wall and Reynolds number rather than the wavelength. 2012 Elsevier Ltd. All rights reserved.